Post-secondary attendance by parental income: Comparing the US and Canada - Philippe Belley; Marc Frenette; Lance Lochner (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2010)
This paper makes three contributions to the literature on educational attainment gaps by family income. First, we conduct a parallel empirical analysis of the effects of parental income on post-secondary (PS) attendance for recent high school cohorts in both the U.S. and Canada using data from the 1997 Cohort of the National Longitudinal Survey of Youth and Youth in Transition Survey. We estimate substantially smaller PS attendance gaps by parental income in Canada relative to the U.S., even after controlling for family background and adolescent cognitive achievement. Second, we develop an intergenerational schooling choice model that sheds light on the role of four potentially important determinants of the family income - PS attendance gap: (i) borrowing constraints, (ii) a 'consumption value' of attending PS school, (iii) the earnings structure, and (iv) tuition policies and the structure of financial aid. Third, we document Canada - U.S. differences in financial returns to PS schooling, tuition policy, and financial aid, discussing the extent to which these differences contribute to the stronger family income - attendance relationship in the U.S. Most notably, we document the dependence of both non-repayable financial aid and government student loan access on parental income in both countries.
Keywords: 330; Haushaltseinkommen; Sozialer Status; Kinder; Bildungsertrag; USA; Kanada